2002
DOI: 10.1007/s00414-002-0297-8
|View full text |Cite
|
Sign up to set email alerts
|

JC virus genotyping offers a new means of tracing the origins of unidentified cadavers

Abstract: There has been no reliable means of tracing the origins of unidentified cadavers but the recent finding that JC virus (JCV) can serve as a means of elucidating human migrations suggested that this virus may also be useful to trace the origins of unidentified cadavers. DNA samples extracted from renal tissue and urine were used as the template for PCR amplification of a 610 bp region (IG region) of the viral genome. We detected JCV DNA in 45% of the renal samples and in 33% of the urine samples and was detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…It was also reported that JC, BK, and Epstein-Barr viruses can be detected at a frequency of 58.3%, 30.5%, and 16%, respectively [Ikegaya et al, 2002[Ikegaya et al, , 2007[Ikegaya et al, , 2008. Compared to these viruses, VZV can be detected at a higher frequency and determination of its genotypes will, therefore, enable the geographical origin of more unidentified cadavers to be determined.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It was also reported that JC, BK, and Epstein-Barr viruses can be detected at a frequency of 58.3%, 30.5%, and 16%, respectively [Ikegaya et al, 2002[Ikegaya et al, , 2007[Ikegaya et al, , 2008. Compared to these viruses, VZV can be detected at a higher frequency and determination of its genotypes will, therefore, enable the geographical origin of more unidentified cadavers to be determined.…”
Section: Discussionmentioning
confidence: 90%
“…A method for identifying cadavers was, therefore, developed as a new source of information. This method determines the geographical origin of unidentified cadavers based on DNA polymorphisms of latent human viruses with different geographical distribution, and previous studies have reported the use of this method for JC, BK, and Epstein-Barr viruses [Ikegaya et al, 2002[Ikegaya et al, , 2007[Ikegaya et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…This geographical identification method using JCV (the JCV method) has already been used in actual police investigations to facilitate identification. Even if the positive rate is high, the JCV method does not always succeed in detecting where people are from [2]. Therefore, we tried to elucidate their geographical origins using another marker, the BK virus (BKV).…”
Section: Introductionmentioning
confidence: 99%
“…There are no reliable means for tracing the geographical origins of unidentified cadavers. Recently, we have reported that the JC virus (JCV), a parasitic agent in human, is useful in tracing the geographical origins of unidentified cadavers [2,3]. JCV is easily detected from the kidney tissue [4] or urine samples [5] of healthy individuals, and it is detectable even from a small urine stain [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the number of unidentified cadavers has increased worldwide (3). The geographic distribution of various viruses has been used to determine the geographic origins cadavers (5)(6)(7)(8)(9). The worldwide distribution of HCV genotypes has also been reported (1, 2, 4, 12-14, 17, 19).…”
mentioning
confidence: 99%